Prevalence of mef and ermB genes in invasive pediatric erythromycin-resistant Streptococcus pneumoniae isolates from Argentina - Corso, Alejandra (2009)
Fil: Corso, Alejandra. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.